Oral anticoagulation in patients with hypertrophic cardiomyopathy and non‐valvular atrial fibrillation in Japan - Hiroaki Kitaoka; Robert Carroll; Natalie Eugene; Bruno Casaes Teixeira; Yukako Matsuo; Toru Kubo (ESC Heart Failure)
Abstract Aims There are limited data to support direct oral anticoagulant (DOAC) use in patients with hypertrophic cardiomyopathy (HCM) and non‐valvular atrial fibrillation (NVAF). The current study investigated the safety and effectiveness of DOACs versus warfarin in patients in Japan. Methods This retrospective observational study assessed a Japanese cohort of patients diagnosed with HCM and NVAF between July 2011 and June 2021 using a Japanese claims database. Propensity score (PS) matching (2:1 DOAC:warfarin) using the nearest‐neighbour method was applied to balance demographic and clinical characteristics between treatment groups. The primary outcomes were the risk of major bleeding and any bleeding (major or minor). Secondary outcomes included describing baseline demographic and clinical characteristics and the risk of stroke/systemic embolism (SE). Results After PS matching, 2955 DOAC‐ and 1603 warfarin‐treated patients were assessed. The mean [standard deviation (SD)] age in the DOAC and warfarin groups was 74.8 (10.5) and 75.3 (10.2) years, respectively. The majority of patients were male (DOAC, 58.8%; warfarin, 59.6%), had comorbidities (DOAC, 97.5%; warfarin, 96.6%), and were treated with β‐blockers (DOAC, 62.5%; warfarin, 62.3%). The risk of major and any bleeding was similar across cohorts [hazard ratio (HR), 0.80; 95% confidence interval (CI), 0.50–1.27; P = 0.336 and HR, 0.93; 95% CI, 0.78–1.11; P = 0.420] while the risk of stroke/SE was lower among patients treated with DOACs (HR, 0.67; 95% CI, 0.47–0.96; P = 0.027). Factors associated with an increased risk of major bleeding included prior bleeding (HR, 1.97; 95% CI, 1.22–3.17) and chronic kidney disease (HR, 1.87; 95% CI, 1.10–3.18). An increased risk of stroke/SE was associated with prior ischaemic stroke (HR, 2.97; 95% CI, 2.05–4.29), peripheral arterial disease (HR, 1.88; 95% CI, 1.22–2.88) and chronic kidney disease (HR, 1.87; 95% CI, 1.24–2.83). Conclusions DOAC‐treated patients had a lower risk of stroke/SE and a comparable risk of bleeding compared with warfarin‐treated patients. Prior stroke was shown to augment stroke risk by approximately three‐fold. This large real‐world study suggests that patients diagnosed with HCM and NVAF can be safely and effectively treated with DOACs in Japan.